Straightforward Generation of Ultrapure Off-the-Shelf Allogeneic CAR-T Cells - Juillerat, Alexandre; Tkach, Diane; Yang, Ming; Boyne, Alex; Valton, Julien; Poirot, Laurent; Duchateau, Philippe (Frontiers in Bioengineering and Biotechnology, 2020)
Here, we developed a straightforward methodology to generate TCRαβ negative (allogeneic) cells for CAR-T cell therapies. With an early and transient expression of an anti-CD3 CAR in the engineered donor T cells, we programed these cells to self-eliminate the TCR+ cell population and obtained an ultrapure TCRαβ- population (99%-99.9%) at the end of the CAR-T production. This novel and easy-to-implement procedure preserves the production yield and cell fitness and has the potential to streamline the manufacturing of “off-the-shelf” CAR T-cell therapies.